2017
DOI: 10.1038/s41467-017-00438-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlated electronic states at domain walls of a Mott-charge-density-wave insulator 1T-TaS2

Abstract: Domain walls in interacting electronic systems can have distinct localized states, which often govern physical properties and may lead to unprecedented functionalities and novel devices. However, electronic states within domain walls themselves have not been clearly identified and understood for strongly correlated electron systems. Here, we resolve the electronic states localized on domain walls in a Mott-charge-density-wave insulator 1T-TaS2 using scanning tunneling spectroscopy. We establish that the domain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
82
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 36 publications
11
82
3
Order By: Relevance
“…This can lead to the emergent corner states at the tri-junctions and corners of the sample boundary, which are akin to those of higher-order topological insulators. [37][38][39] Motivated by references 61,62 where the nature of the insulating domain walls of C-CDW 1T-TaS 2 were discussed, we consider the half-filled wires which can develop a period-2 charge density modulation. When the tri-junction frustrates the charge order and traps solitons, we can show that there is an associated crystal symmetry-protected bound state at the junction (In SI, 41 we provide a few concrete realizations.).…”
Section: (A) the Full Hamiltonian Is Nowmentioning
confidence: 99%
“…This can lead to the emergent corner states at the tri-junctions and corners of the sample boundary, which are akin to those of higher-order topological insulators. [37][38][39] Motivated by references 61,62 where the nature of the insulating domain walls of C-CDW 1T-TaS 2 were discussed, we consider the half-filled wires which can develop a period-2 charge density modulation. When the tri-junction frustrates the charge order and traps solitons, we can show that there is an associated crystal symmetry-protected bound state at the junction (In SI, 41 we provide a few concrete realizations.).…”
Section: (A) the Full Hamiltonian Is Nowmentioning
confidence: 99%
“…Accordingly, in recent years, a significant number of experimental and theoretical studies aimed at pinning down the microscopic mechanism of this non-equilibrium IMT that is believed to be connected to a reorganization of the CDW-order. However, despite significant efforts to determine the microscopic processes underlying this novel IMT have been made [12][13][14][15][16][17], a clear picture remains elusive.In this article we address this open issue directly by means of high-resolution synchrotron x-ray diffraction (XRD) in combination with laser pumping. Our experiments enable examination of the laser-driven transition and in-particular the HCDW-order in 1T-TaS 2 nanosheets with great sensitivity and in all three spatial directions.…”
mentioning
confidence: 99%
“…(d) dI/dV map across the domain wall (domain wall A, DW-A, averaged over longitudinal direction). LHB and UHB are lower and upper Hubbard bands, Ec and Ev indicate the additional conducting and valence bands associated with the Ta d-shell.Single CDW domain walls (DWs) [17,25,32] can be found connecting large lattice inhomogeneities in freshly cleaved samples or they remain after the relaxation of the metastable metallic mosaic state created with voltage pulse from the scanning tunneling microscope (STM) tip. We study both examples and find the relevant physics similar.…”
mentioning
confidence: 99%
“…The long-standing hypothesis for metallisation and SC onset is linked to the formation of CDW domain walls, seen in multiple TMDs with different techniques [22][23][24]. Recently, it was challenged experimentally with scanning tunneling spectroscopy (STS) [25], which showed the absence of metallisation in certain types of walls. First-principles calculations revealed that atomic reconstruction in the walls may cause the formation of bound states [25] and band reconstruction [24], but the correlation effects were left out of scope.…”
mentioning
confidence: 99%
See 1 more Smart Citation